(10x-3y)-(8y+1)=

Simple and best practice solution for (10x-3y)-(8y+1)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (10x-3y)-(8y+1)= equation:


Simplifying
(10x + -3y) + -1(8y + 1) = 0

Remove parenthesis around (10x + -3y)
10x + -3y + -1(8y + 1) = 0

Reorder the terms:
10x + -3y + -1(1 + 8y) = 0
10x + -3y + (1 * -1 + 8y * -1) = 0
10x + -3y + (-1 + -8y) = 0

Reorder the terms:
-1 + 10x + -3y + -8y = 0

Combine like terms: -3y + -8y = -11y
-1 + 10x + -11y = 0

Solving
-1 + 10x + -11y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 10x + 1 + -11y = 0 + 1

Reorder the terms:
-1 + 1 + 10x + -11y = 0 + 1

Combine like terms: -1 + 1 = 0
0 + 10x + -11y = 0 + 1
10x + -11y = 0 + 1

Combine like terms: 0 + 1 = 1
10x + -11y = 1

Add '11y' to each side of the equation.
10x + -11y + 11y = 1 + 11y

Combine like terms: -11y + 11y = 0
10x + 0 = 1 + 11y
10x = 1 + 11y

Divide each side by '10'.
x = 0.1 + 1.1y

Simplifying
x = 0.1 + 1.1y

See similar equations:

| -3+-18r=-345 | | 5x^2+6y+1=0 | | 3(1+6r)=-87 | | 4x+2x+56=180 | | -(2-3p)=p-18 | | 36=8z+20 | | 7/8*2 | | .291666= | | 0.03p+0.05(1300-p)=75 | | 3/x-3×5/2x-6=11/2 | | 3/9=y/12 | | (X+1+2i)(x+1+2i)=0 | | -3r+8+5r+-1= | | 5+2z=2z+6 | | 15x+5=10x | | 5x-3=-9x-7 | | 5+3(5)-(4)(5)= | | w/6=4/8 | | 50x-125= | | 4/3*3.14*7.4 | | 10+x=5(15x+2) | | 10x=15x+5 | | 1/3=-3/5u-1/2 | | 9s-1/3=3/2/3 | | 13=-1/6TH | | x^2+9x-25=0 | | 7x+4-6x=15-20 | | -0.18t=5.2 | | 2x-5=3x-1.50 | | x^20-4x^18+3x-6whenx=2 | | 4a+10a+3=a+42 | | 3/2-8/1 |

Equations solver categories